Les répertoires graphiques amazoniens - Pierre Déléage (Journal de la Société des Américanistes)
Amazonian graphic repertoires. This paper begins with a description of the facial paintings of the Sharanahua, a Panoan people of Western Amazonia. The paintings are created based on a graphic repertoire comprising a series of motifs associated with a specific name. This study presents the principles of composition of these patterns, the mnemotechnical meaning of their names, and the ways they are utilized to create new paintings and make social relationships visible. This repertoire is then compared to those of other Amazonian cultures in order to show evidence for the existence of a homogenous category distinct from that joining together the figurations.